If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -3(2x + -1) = 3x + 1 Reorder the terms: 10 + -3(-1 + 2x) = 3x + 1 10 + (-1 * -3 + 2x * -3) = 3x + 1 10 + (3 + -6x) = 3x + 1 Combine like terms: 10 + 3 = 13 13 + -6x = 3x + 1 Reorder the terms: 13 + -6x = 1 + 3x Solving 13 + -6x = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 13 + -6x + -3x = 1 + 3x + -3x Combine like terms: -6x + -3x = -9x 13 + -9x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 13 + -9x = 1 + 0 13 + -9x = 1 Add '-13' to each side of the equation. 13 + -13 + -9x = 1 + -13 Combine like terms: 13 + -13 = 0 0 + -9x = 1 + -13 -9x = 1 + -13 Combine like terms: 1 + -13 = -12 -9x = -12 Divide each side by '-9'. x = 1.333333333 Simplifying x = 1.333333333
| 0.75=75/100 | | 4x-1+26=p | | 3xy*(4x-5y)= | | 5-20=8x-4-7x | | 8a-(a-4)= | | 2h-8=10-4h | | 7y-3=3y+25 | | 42+5=71 | | 2ba+3ab= | | 1/2X1/2=2/5 | | logx(20)=3 | | 3y-11=21 | | 3x+m=16 | | -2.8/7 | | factorisemn=m | | 3(2x-1)=x+27 | | 15-4(2a-1)= | | 3(x-4)=24 | | 4cosx+1=0 | | y=9x^3-7x+2 | | 4c-1=-5 | | 12t=howmenylb | | X+7.1=4.1 | | 3p^2-6p=1 | | 187=88-y | | 1+(4*4)-2= | | S+4.1=8.1 | | 1*10= | | n^2/3-n/6 | | 52x+3=1 | | (3/4)n | | y^2/2=32 |